Preparing for your migration to the cloud : 7 steps to success - Francis, Steve (O'Reilly Media, 2019)
The great cloud migration is picking up steam. Companies moving all or part of their IT workloads to the public cloud for backup, email hosting, productivity apps or all of the above will generate $44 billion in costs during 2018 alone. So, the question is not if but how enterprises plan to make the move. This ebook provides a practical seven-step migration plan to prepare your company for the journey. Author Steve Francis provides a prescriptive look at the best practices needed to ensure a successful transition. You'll also learn from several IT and business leaders about their recent cloud migration experiences, including pitfalls to avoid. This seven-step plan focuses on three major benefits of the cloud: operational agility, strategic focus, and cost savings: Identify desired outcomes before you get into migration specifics Classify candidates for the cloud, including applications or workloads best suited for the move Define deployment model criteria--IaaS, PaaS, SaaS, or a private cloud Devise an iterative, agile process for transformation among your teams Get buy-in to the plan from people at the top and in the trenches Start simply with a project that's relatively risk-free--one you're likely to learn from the most Rinse and repeat by applying lessons learned to the next workload or application.